Topsy-Turvy Heart with Aortopulmonary Window and Severe Airway Malacia: Prenatal Diagnosis and Review of the Literature - Yahia Hejazi (14150136) (2022)
The topsy-turvy heart is a very rare cardiac malformation that involves a global 90° clockwise rotation of the heart along its long axis. This rotation results in the displacement of the great arteries and severe elongation and stretching of the brachiocephalic arteries and the bronchi. We present an unusual case of topsy-turvy heart diagnosed prenatally with a large aorto-pulmonary window and. This case gives an insight into the morphological details and clinical presentation of this rare malformation and its associated complications. We also present a review of the literature of this rare anomaly showing only 15 live cases that have been published with only three cases diagnosed prenatally. Other Information Published in: Pediatric Cardiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00246-021-02710-1